2017
DOI: 10.3389/fphar.2017.00204
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Reveals Autophagy as Pro-Survival Pathway Elicited by Long-Term Exposure with 5-Azacitidine in High-Risk Myelodysplasia

Abstract: Azacytidine (5-AZA) is the standard first-choice treatment for high-risk myelodysplasia (MDS) patients. However, the clinical outcome for those patients who interrupt treatment or whose disease failed to respond is very poor. In order to identify the cellular pathways that are modified by long-term exposure to 5-AZA, we evaluated key proteins associated with the autophagy pathway by reverse-phase microarray (RPPA). Comparing bone marrow mononucleated cells (BMMCs) obtained from 20 newly-diagnosed patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In addition to the inhibition of Notch signaling, expression of autophagy genes (LC3I/II, BECLIN) was enhanced upon DAPT treatment, in a dose-dependent manner. Most recent data show that bone marrow mononucleated cells exposed to 5-Azacytidine express increased proteins associated with autophagy (46). Hence, it could be hypothesized that autophagy plays a role in neuronal differentiation, once Notch singling is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibition of Notch signaling, expression of autophagy genes (LC3I/II, BECLIN) was enhanced upon DAPT treatment, in a dose-dependent manner. Most recent data show that bone marrow mononucleated cells exposed to 5-Azacytidine express increased proteins associated with autophagy (46). Hence, it could be hypothesized that autophagy plays a role in neuronal differentiation, once Notch singling is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of autophagy has been shown to promote the survival of cancer and cancer-related cells treated with a variety of therapeutics including tamoxifen, paclitaxel, epirubicin, and azacytidine [14][15][16][17][18]. Autophagy is also known to assist homologous recombination, which is a type of DNA repair mechanisms, in cells treated with DNA damaging agents and UV radiation [91][92][93].…”
Section: Bruce Mediates Homologous Recombination and Autophagosome-lymentioning
confidence: 99%
“…Autophagy is currently one of the hottest topics in cancer research. Despite intensive research has been conducted in the past decade to better understand the process of autophagy [13][14][15][16][17][18][19][20][21][22][23], the detailed regulatory mechanism and cellular effects are still not yet fully understood. Generally, autophagy is a dynamic catabolic process used for removing unnecessary or dysfunctional proteins and organelles in cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, we investigated the potential benefit of autophagy inhibition as a new approach to increase the anti-leukemic activity of the hypomethylating agent azacitidine (AZA) [8]. Recent studies have shown that autophagy plays a role in resistance to AZA, which is frequently used in the management of patients with myelodysplastic syndromes (MDS) and AML [9, 10]. We showed that the combination of ROC-325 and AZA blocked AZA-induced autophagy and yielded significantly improved activity against AML cell lines and primary AML blasts.…”
mentioning
confidence: 99%